Understanding the Final Disposition of Livers Declined After the Start of Procurement: A Nationwide Organ Procurement Organization Effort. Issue 2 (11th February 2021) - Neidlinger, Nikole A.; Brown, Christopher; Wood, Patrick; Traseger, Jeff; Lebovitz, Dan; Cauwels, Roxane; Syed, Shareef; Parekh, Justin R.; Roll, Garrett R.
Abstract : Declining a liver offer during organ procurement likely increases the risk of discard, but the specifics around late reallocation remain obscure. This voluntarily submitted, prospectively collected data describe late declines and the ultimate disposition of 893 livers. Once a liver suffered an intraoperative decline, only 49% of recovered livers were transplanted. Livers declined ≥80 minutes prior to cross‐clamp were transplanted 80% of the time versus livers declined ≥80 minutes after cross‐clamp, which were transplanted 45% of the time. The final disposition of these livers was into a predetermined backup patient (51%) or required an out‐of‐sequence expedited allocation (42%). Prerecovery imaging and prerecovery biopsy did not influence the ability to reallocate a liver, and livers from donors after circulatory death are rarely successfully reallocated. In conclusion, this study begins to shed light on this seemingly common practice. A total of 85% of centers had an intraoperative decline, but 4% of centers accounted for 25% of the declines. Organ procurement organizations often enter expedited liver allocation, and instituting a cross‐clamp delay to allow for reallocation may influence the disposition of these liver grafts. Expedited allocation was more time consuming than allocation into a predetermined backup. Although a certain number of intraoperative declines probably suggests a healthy amount of donor selection aggressiveness at the time of the initial organ offer, the 47% risk of discard of livers declined intraoperatively suggests that United Network for Organ Sharing should consider systematically collecting data about intraoperative declines so we can learn more about this event that influences organ utilization.